2018
DOI: 10.2140/apde.2018.11.213
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency approximation of the interior Dirichlet-to-Neumann map and applications to the transmission eigenvalues

Abstract: Abstract. We study the high-frequency behavior of the Dirichlet-to-Neumann map for an arbitrary compact Riemannian manifold with a non-empty smooth boundary. We show that far from the real axis it can be approximated by a simpler operator. We use this fact to get new results concerning the location of the transmission eigenvalues on the complex plane. In some cases we obtain optimal transmission eigenvalue-free regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 15 publications
0
48
0
Order By: Relevance
“…We obtain here a conditional monotonicity property for the largest positive Steklov eigenvalue. In the following theorem we give the optimal condition on A, n and k which ensure the coercivity property (25), whence the sup-condition (27). (20).…”
Section: Steklov Eigenvaluesmentioning
confidence: 99%
“…We obtain here a conditional monotonicity property for the largest positive Steklov eigenvalue. In the following theorem we give the optimal condition on A, n and k which ensure the coercivity property (25), whence the sup-condition (27). (20).…”
Section: Steklov Eigenvaluesmentioning
confidence: 99%
“…Having high-frequency approximations of the DN map proves very usefull when studying the location of the complex eigenvalues associated to boundary value problems with dissipative boundary conditions or to interior transmission problems. In particular, this proves crucial to get parabolic transmission eigenvalue-free regions (see [9], [10], [11], [12]). As an application of our parametrix we improve the transmission eigenvalue-free region obtained in [12] in the case of the degenerate isotropic interior transmission problem (see Theorem 4.1).…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…The best to date result for Maxwell's equations is presented in [8], where more precisely it is shown that transmission eigenvalues lie inside any arbitrary small wedge around the real and imaginary axis. In contrast, for the scalar case of Helmholtz equation, much finer results on the location of transmission eigenvalues are available [15,20,21,22,23]. More importantly, for the Helmholtz equation, Vodev [23] is the first to show that for inhomogeneities with smooth support and coefficients, there are no transmission eigenvalues outside a horizontal strip around the real axis, i.e.…”
mentioning
confidence: 99%
“…In contrast, for the scalar case of Helmholtz equation, much finer results on the location of transmission eigenvalues are available [15,20,21,22,23]. More importantly, for the Helmholtz equation, Vodev [23] is the first to show that for inhomogeneities with smooth support and coefficients, there are no transmission eigenvalues outside a horizontal strip around the real axis, i.e. all transmission eigenvalues have imaginary part uniformly bounded, under certain conditions for the contrasts of the medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation